2011
DOI: 10.2139/ssrn.1944685
|View full text |Cite
|
Sign up to set email alerts
|

Planned Behavior Entrepreneurship and Intention to Create New Venture Among Young Graduates

Abstract: This paper attempts to investigate whether young graduates possess the leadership style that is pre-requisite to become entrepreneur. The paper further examines the role of higher education towards the desire of new venture creation among young graduates in developing economies specially. This study analyzed the response of 225 final-semester students at different universities in Islamabad, Rawalpindi and Lahore. A questionnaire based survey instrument was used. Result of the present study shows that education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Besides prior studies which support the general notion that professional attraction contributes to entrepreneurial intention [10][11][12], also found significant relationship between professional attraction and entrepreneurial intention by using Structural Equation Modeling (SEM). Hence, the following hypothesis is proposed: H 1 : Professional attraction has a positive direct effect on entrepreneurial intention…”
Section: Introductionsupporting
confidence: 54%
“…Besides prior studies which support the general notion that professional attraction contributes to entrepreneurial intention [10][11][12], also found significant relationship between professional attraction and entrepreneurial intention by using Structural Equation Modeling (SEM). Hence, the following hypothesis is proposed: H 1 : Professional attraction has a positive direct effect on entrepreneurial intention…”
Section: Introductionsupporting
confidence: 54%
“…Entrepreneurial intention is the first step in the formation of new businesses (Lee & Wong, 2004). Economic motivation and individual independence are the main driving forces that create the entrepreneurial intention (Hunjra, Ahmad, Ur-Rehman, & Safman, 2011).…”
Section: Entrepreneurship Developmentmentioning
confidence: 99%
“…According to Johannisson (2000), those who have the entrepreneurial intention and entrepreneurial capability can gain access to information and finance sources that are useful through a network of entrepreneurship. Through the network, each person can take steps to develop their entrepreneurial abilities (Tian, Wang, Chen, & Johansson, 2009) and expand their own business (Hunjra, Ahmad, Ur-Rehman, & Safman, 2011). When a network of entrepreneurs' entrepreneurship starts to contribute towards the objectives of their entrepreneurship, this social contact will become their social capital (Burt, 1992), it is because the network provides an easy approach to obtain finance and experienced workforce in ensuring the development of entrepreneurship (Hellman & Puri, 2002).…”
Section: Entrepreneurship Developmentmentioning
confidence: 99%
“…Meanwhile, the eight-item instrument developed by [29] measures an individual's tendency to implement entrepreneurial activities over the next 12 months. [30] also developed a six-item questionnaire relating to organized behavior among young graduates and the intention to start a new business. Based on the questions to be answered, this study chose to use the instrument developed by [28] to identify the level of entrepreneurial intention because the focus of the study was similar and the sample was also students.…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…Furthermore, scholars also searched for answers to whether entrepreneurship education could be related to and influence entrepreneurial intention directly. A study by [30] found that entrepreneurship education could influence entrepreneurial intention through the exposure of relevant skills during the education process. In other words, students were more willing and prepared to start a business after they received business and entrepreneurship-related education.…”
Section: Entrepreneurship Educationmentioning
confidence: 99%